Politik Hukum dalam Legislasi Daerah: Tantangan dan Strategi Meningkatkan Kualitas Peraturan di Indonesia - Rizkisyah, Renofadli; Triadi, Irwan (Indonesian Journal Publisher, 2024)
Regional regulations are written rules that are generally binding and enacted by the Regional People's Representative Council (DPRD) in collaboration with the Regional Head. The formulation of regional regulations through the regional legislative program holds a strategic role in ensuring that these regulations align with societal needs. However, many regional regulations face public rejection or are annulled by the government. This study employs a normative legal approach to analyze these issues. The findings reveal that the lack of public involvement during the drafting process is a significant factor contributing to the unacceptability of these regulations. Furthermore, the absence of political will from regional governments and DPRD to systematically develop regulations based on academic studies exacerbates the problem. It is imperative for regional governments and DPRD to first establish a legislative program grounded in the actual needs of the community, adhering to the Regional Medium-Term Development Plan (RPJMD) or the Regional Strategic Plan (Renstra). Collaboration with universities to conduct academic studies can provide a strong scientific basis for drafting academic manuscripts before regulations are legalized. In conclusion, a systematic and collaborative approach is essential to improve the quality of regional legislation, ensuring responsiveness to public needs and supporting regional development.